Speedy Recovery of Subcutaneous Abscess and The Presence of Overgrown Nails in A Pygmy Hedgehog: A Case Report - Budiono, Novericko Ginger; Wen, Nicole Ting Qian; Rajendran, Punithe Raj A/L; Proboningrat, Annise (Jurnal Medik Veteriner, 2023)
This study reported that a 15-month-old intact female African pygmy hedgehog (Atelerix albiventris) was presented to IPB University Veterinary Teaching Hospital to evaluate a 1.5 cm í— 1.5 cm í— 0.5 cm mass on the left ventral thorax, three days after the mass was first discovered by the owner. Overgrown nails were observed on all four toes of each of the four limbs of the hedgehog. The body weight was 150 g, and the axial temperature was 36.5°C. The heart and respiratory rates were 180 per minute and 40 per minute, respectively. After a thorough physical examination, the patient was diagnosed with subcutaneous abscesses and overgrown nails. The abscess was surgically resected using a local anesthetic. The overgrown nails were trimmed to prevent further injury and the recurrence of abscesses. Following surgery, the hedgehog was discharged directly from the hospital and treated using Amoxicillin 15 mg/kg per oral every 12 hours for seven days, daily routine wound cleaning with sodium chloride, and topical powder of neomycin sulfate 5 mg/g and bacitracin 250 IU/g. The patient responded effectively to the systemic treatment, and medical signs and symptoms resolved. The hedgehog fully recovered from the subcutaneous abscess 14 days after the first hospital visit. No recurrence was reported in the subsequent month after resolution.